Togra Mashhadhi and his Rasaeil - محمدحسن حائری; سید محمّد صاحبی (تاریخ ادبیات)
Togra Mashhadhi is one of the poets and writers of the 11th century. In this article, the life and circumstances of Togra Mashhadi are described, his thoughts are examined, the theory and literary criticism in his works are discussed, and there are discussions about his opinion on plagiarism. Then, in a brief way, things were raised about Togra's poems and their type and style, and more broadly, the quantity and quality of his Rasaeil were discussed. The style of Rasaeil has been analyzed on two linguistic and literary levels. The article ends with a discussion about the structure of Togra's Rasaeil. This research has been done using the manuscripts of the works of Togra Mashhadhi.